Motilin-induced gastric contractions signal hunger in man. Issue 2 (24th December 2014) - Tack, J; Deloose, E; Ang, D; Scarpellini, E; Vanuytsel, T; Van Oudenhove, L; Depoortere, I
Abstract : Rationale: Hunger is controlled by the brain, which receives input from signals of the GI tract (GIT). During fasting, GIT displays a cyclical motor pattern, the migrating motor complex (MMC), regulated by motilin. Objectives: To study the relationship between hunger and MMC phases (I–III), focusing on spontaneous and pharmacologically induced phase III and the correlation with plasma motilin and ghrelin levels. The role of phase III was also studied in the return of hunger after a meal in healthy individuals and in patients with loss of appetite. Findings: In fasting healthy volunteers, mean hunger ratings during a gastric (62.5±7.5) but not a duodenal (40.4±5.4) phase III were higher (p<0.0005) than during phase I (27.4±4.7) and phase II (37±4.5). The motilin agonist erythromycin, but not the cholinesterase inhibitor neostigmine, induced a premature gastric phase III, which coincided with an increase in hunger scores from 29.2±7 to 61.7±8. The somatostatin analogue octreotide induced a premature intestinal phase III without a rise in hunger scores. Hunger ratings significantly correlated (β=0.05; p=0.01) with motilin plasma levels, and this relationship was lost after erythromycin administration. Motilin, but not ghrelin administration, induced a premature gastric phase III and a rise in hunger scores. In contrast to octreotide, postprandial administration of erythromycin induced a premature gastric phase III accompanied by an early rise in hunger ratings. In patients with unexplained loss of appetite, gastric phase III was absent and hunger ratings were lower. Conclusions: Motilin-induced gastric phase III is a hunger signal from GIT in man.